The Forkhead factor FoxQ1 influences epithelial differentiation - Feuerborn, Alexander; Srivastava, P. K.; Küffer, Stefan; Grandy, W. A.; Sijmonsma, T. P.; Gretz, Norbert; Brors, Benedikt; Gröne, Hermann-Josef (Journal of cellular physiology, 2011)
The Forkhead family of transcription factors comprises numerous members and is implicated in various cellular functions, including cell growth, apoptosis, migration, and differentiation. In this study, we identified the Forkhead factor FoxQ1 as increased in expression during TGF-β1 induced changes in epithelial differentiation, suggesting functional roles of FoxQ1 for epithelial plasticity. The repression of FoxQ1 in mammary epithelial cells led to a change in cell morphology characterized by an increase in cell size, pronounced cell-cell contacts, and an increased expression of several junction proteins (e.g., E-cadherin). In addition, FoxQ1 knock-down cells revealed rearrangements in the actin-cytoskeleton and slowed down cell cycle G1-phase progression. Furthermore, repression of FoxQ1 enhanced the migratory capacity of coherent mammary epithelial cells. Gene expression profiling of NM18 cells indicated that FoxQ1 is a relevant downstream mediator of TGF-β1-induced gene expression changes. This included the differential expression of transcription factors involved in epithelial plasticity, for example, Ets-1, Zeb1, and Zeb2. In summary, this study has elucidated the functional impact of FoxQ1 on epithelial differentiation. J. Cell. Physiol. 226: 710-719, 2011. © 2010 Wiley-Liss, Inc.
First published: 17 August 2010
Gesehen am 05.05.2022